Analysis Of The Influence Of Fake Discount Price Labels For A Product In The Marketplace On The Concept Of Business Competition And Responsibility - Fadhilla, Suci Rizka; Dini, Nia Rahma; Wolontery, Sylvira Agshelya (PT. Anagata Sembagi Education, 2024)
The influence of fake discount price labels on products in the marketplace on the concept of business competition and liability for losses experienced by consumers is an interesting topic to discuss in the ins and outs of marketplace problems in Indonesia. One of the famous marketplaces in Indonesia, namely Shopee, harbors many fraudulent practices in product sales by sellers, such as the use of fake discount price labels. Due to this, consumer trust is damaged and unhealthy business competition occurs. This research uses normative juridical legal research methods and collects secondary data from scientific sources, regulations and websites. Including fake discount price labels that do not match the actual price can harm consumers immaterially. This action violates various regulations, such as the Consumer Protection Law. The parties responsible for the losses experienced by consumers are sellers who promote fake discount prices in the marketplace. Therefore, it is necessary to discuss the influence of fake discount price labels on the concept of business competition and how to be held accountable for losses experienced by consumers